Light-Free Cross-Talk Analysis of a CMOS Infrared Detector Array - Ying Dai; Syed Zeeshan Ali; Richard Hopper; Claudio Falco; Daniel Popa; Florin Udrea (Proceedings, 2020)
Low-cost infrared (IR) thermal cameras are powering a rising market of industrial and consumer applications. Complementary metal-oxide-semiconductor (CMOS)-based thermopile arrays are proven thermal imagers that can be monolithically integrated into low-cost and low-power-consumption formats for high-volume manufacturability. Here we present a simple method to evaluate the cross-talk of these arrays and propose a numerical model for device optimization.